PITUITARY METASTASIS: A RARE PRESENTATION OF SMALL CELL LUNG CANCER - Mok, Meng Loong; Chai, Shu Teng; Roy, Vivithirah K. Arjunan; Shamsudin, Norsarah (Journal of the ASEAN Federation of Endocrine Societies, 2023)
INTRODUCTION/BACKGROUND The pituitary gland is a rare site for metastasis, with breast and lung cancers being the most common primary malignancies implicated in such instance. Most pituitary metastasis are clinically silent and diagnosed incidentally during radiological evaluation of brain metastasis. CASE We describe an elderly male, who had advanced small cell lung carcinoma diagnosed after his initial presentation of left cerebellar and pituitary metastatic lesions. A 77-year-old ex smoker complained of headache and vomiting for six months. Brain MRI showed a left cerebellar cystic lesion (3.9 x 4.6 x 3.3 cm) with mass effect. Additionally, a lobulated pituitary mass with posterior pituitary involvement and suprasellar extension was seen (1.3 x 1.3 x 1.0 cm and 1.2 x 1.4 x 1.0 cm for sellar and suprasellar components respectively). Following excision of the left cerebellar lesion, the patient was discharged. Ten days later, he was readmitted for hospital-acquired infection with transient hypotension. Stress dose of hydrocortisone was commenced for a low morning cortisol of 81.8 nmol/L. Both subnormal TSH (0.047 mIU/L; Normal: 0.35 – 4.94) and free T4 (8.59 pmol/L; Normal: 9.01 – 19.05) were attributed to sick euthyroidism. Prolactin was slightly elevated. There was no diabetes insipidus. A right upper lobe lung mass with mediastinal and right hilar lymphadenopathy were evident from contrastenhanced CT thorax, abdomen, and pelvis. Endoscopic ultrasound guided fine-needle biopsy of aortopulmonary node was performed. Histopathological examinations of both specimens (aortopulmonary node and cerebellar mass) were consistent with small cell lung carcinoma. He subsequently underwent whole brain radiotherapy. Unfortunately, he passed away during the treatment course. CONCLUSION Pituitary metastasis is rare and exhibits a predilection for the posterior pituitary. Clinical manifestations of pituitary metastasis, if present, include visual field defects, cranial diabetes insipidus, anterior pituitary hormone deficiency, and headache. Its presence should be suspected when a pituitary tumour involves the posterior pituitary, especially in an elderly patient.